Prospecção metagenômica e cultivo-dependente de substâncias bioativas produzidas por bactérias associadas aos moluscos da família Teredinidae e estudo da citotoxicidade do tartrolon D - Brito, Thaís Lima (2018)
Microorganisms from special ecological niches, such as the marine invertebrate symbionts, are a source of several natural products. A classic model of symbiosis occurs between the bivalve mollusks of wood borings of the family Teredinidae and an abundant population of γ-proteobacteria that inhabit the gills of the animal. These bacteria help in the nutrition and chemical defense of the host, through the production of enzymes such as glycosyl hydrolases and toxic compounds such as tartrolons. However, the metabolic potential of these endosymbionts is still far from fully explored. This study is divided into two chapters. In the first one, we aimed prospect bioactive substances produced by teredinidae’s symbionts through the integration of massive shotgun type sequencing and microbial culture dependent techniques. In the second, the objective was to evaluate the cytotoxic potential of the tartrolon D compound produced by the endosymbionts. First of all, 19 teredinids were collected and identified as belonging to the species Neoteredo reynei, Lyrodus massa and Bankia sp.. The metagenomic DNA of the gills, digestive glands and intestine of 3 N. reynei specimens was sequenced and taxonomic and functional signatures were analyzed. It was verified that the gills samples are enriched (abundance> 80%) for hits of the Bacteria domain, but this microbioma is little diverse, being constituted mostly by γ-proteobacteria. The intestinal and digestive gland samples, on the other hand, have a discrete microbial population, but cover a greater diversity of associated classes. In addition to being enriched of hits for α-proteobacteria and negativicutes in relation to the gills. The profile of the functional signatures is similar between microbiomes, but the gills have some enrichment of functions that help in their interaction with the host, such as the function of nitrogen metabolism and synthesis, and the function of iron capture and metabolism. From the cross-assembly and batching, two genomes were recovered from the gill metagenomes. The tissues were processed, homogenized and plated in SBM-S and SMB-C medium in serial dilutions. Cultures were grown in SBM-C or SBM-S broth and cryopreserved. When cultivating the homogenates of the gills, intestines and digestive glands, 247 strains were isolated. Ethyl acetate solvent was used for the production of organic extracts of 46 bacteria, however 14 crude extracts were considered active (inhibition of growth> 75%) in HCT 116 human colorectal cancer cells at 50 μg / mL concentration after 72 h of incubation. The mean inhibitory concentrations (IC50) were estimated for the active extracts and ranged from 0.6 to 26 μg / mL. In parallel, the taxonomic identification of 46 isolates showed that the cultivable microorganisms of the species of Neoteredo reynei and Lyrodus mass are composed mainly by bacteria of the proteobacteria, actinobacteria and firmicutes phyla. The antiproliferative effect of tartrolon D was investigated by the SRB assay in 4 normal (L929 and HEK293A) tumor lines (HCT 116, B16-F10, PC-3M and MCF-7). The compound was able to produce a cytostatic and cytotoxic effect in all strains evaluated, with emphasis on HCT 116 and B16F-10 strains, which were more sensitive to treatment with IC 50 equivalent to 0.04 μM and 0.3 μM, respectively. Through differential staining, some morphological changes were observed in HCT 116 cells when incubated with the compound for 24 hours. These changes include mitotic figures, membrane instability, DNA fragmentation, and the reduction of cell volume accompanied by chromatin condensation. In addition, the analysis of the cell morphology by flow cytometry showed an increase in the populations of cells with high granularity and with reduced size after 48h of incubation with 24.3 μM of tartrolon D. The decrease in cell numbers and the increase in percentages of non-viable cells were also detected for the highest concentration tested. The cell cycle profile of HCT 116 cells incubated with 24.3 μM of the compound for 24 and 48 hours demonstrated accumulation of DNA in G2 / M, and increased DNA fragmentation. Previously, no previous study of mechanism of action had been performed with tartrolon D.